PENGEMBANGAN BAHAN AJAR BERBASIS SOFTWARE MATLAB PADA MATA KULIAH METODE NUMERIK: Materi pembelajaran: Metode penghampiran fungsi: Matlab - Rikayanti Rikayanti (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2017)
Teaching materials is one of the important aspects of a lecture process, in which there are clues to how a student can achieve the target lectures. Algorithm is a major part of the numerical course that is widely used in various disciplines, such as data processing of experimental results, as well as in product sales model. Through the application of Matlab software, mastery of the algorithm in solving problems with various methods can be tested. The research method used is Research and Development, while the development model using Didaktis Design Research (Didactical Design Research / DDR). Mathematics Education Study Program Faculty of Teacher Training and Education University Singaperbangsa Karawang, is the place of research implementation. This research involves students contracting numerical course courses conducted in the semester V. Matlab programming packages provide the thinking space of the user in designing a problem solving which is then translated into the corresponding instructions. Given the limitations of teaching-learning variations or textbooks with software-based, it is hoped that the outcomes of this research can add references and reading materials to those interested in applied mathematics. Keywords: teaching materials, curve matching method, matlab software